(untitled) (Research, Society and Development, 2022)
Green banana biomass (GBB) can be used as a functional and technological ingredient in various food preparations, making them healthier and more nutritious. The aim of the present study was to determine the physicochemical compositions as well as color parameters of different GBB samples, and applying them to gnocchi pasta to determine the resulting technological and cooking properties. The bananas (‘BRS Platina, ‘Fhia 01,’ and ‘Fhia 18’) were grown in an area of the Agroecological Production Integrated System, in Seropédica-RJ, Brazil; the bananas were harvested unripe and pressured cooked to obtain their biomass. The pH values, total titratable acidity, total soluble solids, reducing sugars, moisture, ash, proteins, lipids, total starch, total energetic value (TEV), vitamin C, total phenolic compounds (TPC), minerals, and color were significantly different among the different GBB samples used. Each GBB showed different values of certain analyzed parameters; for instance, ‘BRS Platina’ presented low contents of total starch, lipids, TEV and high levels of vitamin C and TPC. The GBB ‘Fhia 01’presented the highest levels of moisture, proteins, and potassium. All GBBs provided good technological attributes (cooking time, weight increase, cooking loss, and volume increase) for the prepared gnocchi dough. Overall, the application of GBB as an ingredient in gnocchi formulation provided good technological quality and increased nutritional value, thus meeting the growing demand of the consumer market for products with greater health benefits.